2015
DOI: 10.1016/j.myc.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships among biological species of Armillaria from China

Abstract: Highlights• Phylogenetic relationships among Armillaria species from China were determined.• Four main phylogenetic lineages were identified for Chinese Armillaria isolates.• Unnamed biological species from China grouped in the "A. gallica cluster". Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 48 publications
4
36
0
Order By: Relevance
“…gallica and A . sinapina , based on phylogenetic analyses of the IGS-1 region [ 26 ]. Although no compatibility reaction emerged between the isolates of CBS F and European or North American A .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…gallica and A . sinapina , based on phylogenetic analyses of the IGS-1 region [ 26 ]. Although no compatibility reaction emerged between the isolates of CBS F and European or North American A .…”
Section: Discussionmentioning
confidence: 99%
“…Among these, it was shown that tef1 - α could successfully distinguish closely related Armillaria biological species, which has also been revealed by other researchers [ 21 25 ]. Based on the sequences from tef1 - α and IGS-1, a recent study by Coetzee et al [ 26 ] elucidated the phylogenetic relationships among biological species of Armillaria from China, and generally resolved four main phylogenetic groups, namely, the “ A . ostoyae ”, “ A .…”
Section: Introductionmentioning
confidence: 99%
“…ostoyae (Hanna, Klopfenstein, Kim, McDonald, & Moore, ; Keča & Solheim, ; Kim et al., ; Pérez‐Sierra, Guillaumin, Spooner, & Bridge, ). Of late, the translation elongation factor‐1 alpha ( tef 1) region has successfully been used to distinguish Armillaria species that ITS or IGS could not separate (Antonín et al., ; Brazee et al., ; Coetzee, Wingfield, Zhao, van Coller, & Wingfield, ; Elías‐Román et al., ; Guo et al., ; Hasegawa et al., ; Klopfenstein et al., ; Maphosa, Wingfield, Coetzee, Mwenje, & Wingfield, ; Mulholland et al., ; Ota, Kim, Neda, Klopfenstein, & Hasegawa, ; Ross‐Davis, Hanna, Kim, & Klopfenstein, ; Tsykun et al., ). On the basis of a recent multilocus phylogenetic study that included tef 1, the taxonomy of some Armillaria species was revised in species that lack an annulus on the stipe.…”
Section: Introductionmentioning
confidence: 99%
“…Armillaria (Basidiomycota; Physalacriaceae) is genus of approximately 40 described species of white rot pathogens that cause Armillaria root disease on hundreds of plant species (Baumgartner, Coetzee, & Hoffmeister, 2011;Guillaumin & Legrand, 2013;Raabe, 1962; Royal Horticultural Society (RHS) Advisory Service, 2015). It is a global problem: in Canada, over 200 million hectares of forests are affected by Armillaria root disease (Canadian Forest Service, 2014;Chapman & Schellenberg, 2015;Cruickshank, 2011); Armillaria infections are also reported from forests across Europe and North and South America (Brazee, Marra, & Wick, 2012;Ferguson, Dreisbach, Parks, Filip, & Schmitt, 2003;Heinzelmann, Rigling, & Prospero, 2012;Labbé et al, 2015) as well as commercial orchards and vineyards (Baumgartner, 2004;Elías-Román et al, 2013;Pellegrini, Prodorutti, & Pertot, 2014;Schnabel, Rollins, & Henderson, 2011), and Armillaria root disease is problematic in Africa, Asia, and Australasia (Coetzee, Wingfield, Zhao, Van Coller, & Wingfield, 2015;Hood, Oliva, Kimberley, Arhipova, & Bakys, 2015;Wingfield, Maphosa, Coetzee, Mwenje, & Wingfield, 2009). Ornamental plants, including herbaceous species, are also affected (Blaedow, Baumgartner, Cox, & Schnabel, 2010;Coetzee et al, 2001;Travadon et al, 2012) and in the UK the majority of enquires received by the RHS Advisory Service over the past 19 years regarding plant diseases in UK gardens have been concerning Armillaria (RHS, 2015).…”
Section: Introductionmentioning
confidence: 99%